Crystal structure of 2-[bis(benzylsulfanyl)methyl]-6-methoxyphenol - Abhinav Raghuvanshi (Acta Crystallographica Section E: Crystallographic Communications, 2020)
The title compound, C22H22O2S2, 1, represents an example of an ortho-vanillin-based functionalized dithioether, which could be useful as a potential chelating ligand or bridging ligand for coordination chemistry. This dithioacetal 1 crystallizes in the orthorhombic space group Pbca. The phenyl rings of the benzyl groups and that of the vanillin unit form dihedral angles of 35.38 (6) and 79.77 (6)°, respectively. The crystal structure, recorded at 100 K, displays both weak intramolecular O—H...O and intermolecular O—H...S hydrogen bonding.